Job Satisfaction of Health Professionals Working in Governmental Tertiary Level Hospitals of Nepal (American Journal of Medical Science and Innovation, 2023)
The extent to which an individual feels self-motivated, content & satisfied with his/her job is job satisfaction. By enhancing job satisfaction among the employees, the organization can creates happier employees. It will eventually lower costs for hiring and training new personnel and also create more motivated and productive employees. This descriptive study was carried out to find out the various factors that influence job satisfaction of health employees of varying specializations working in a tertiary level Governmental Hospital of Nepal. The participants were asked to respond the questionnaires largely based upon the Job Satisfaction Scale (JSS) questionnaires developed by Paul E. Spector (1997) using 5-point likert scale. Convenience sampling method was employed in the study. Similarly, the study also relied on the publications of the various related agencies for its secondary sources in regard to data collection. Only 28.1% of the participants were found to be satisfied. The study proposes that hospital employees perceive supervision, recognition, pay& benefits, promotion, work environment and autonomy as significant factors affecting their job satisfaction. Also demographic variables like age, rank and education qualification has a significant relationship with job satisfaction while gender, marital status and work experience didn’t show any significant correlation with job satisfaction. The study provides an insight to the policy makers about the various factors that need to be considered for uplifting the job satisfaction level of the health professionals and hence uplifting the standard of the health care system of the Governmental Hospital.